Floristic importance of phyllanthus amarus schumach & thonn in selected farming communities and its domestication in Oyo state, Nigeria (2019)
Phyllanthus amarus is a pantropic weed with numerous medicinal uses. It is collected in the wild, often in unwholesome environment and is hardly available all year round, which calls for its domestication for eventual cultivation. The distribution and seedling growth of P. amarus were studied in two seasons at two farming communities in Oyo State, Nigeria. A 25 x 25 m plot was marked out in Akufo and Fiditi. Fifteen quadrats (50 x 50 cm) were randomly placed using x-y ordinate system to enumerate and determine Relative Importance Value (RIV) for all low growing plants. Growth and dry matter accumulation of seedlings were monitored in a pot trial in clay and sandy-loam soils, combined with four watering intervals (1, 2, 3 and 7 days). Data were analysed using ANOVA and means separated by Least Significant Difference at 5% level of probability. Results showed that Phyllanthus amarus is more abundant at Fiditi (RIV=47.16%) than Akufo (RIV=9.15%) at the onset of wet season but reduced at the mid wet season. It performed best (P ≤ 0.05) on sandy-loam soil and daily watering significantly effected its best growth and dry matter yield. Phyllanthus amarus responded positively to daily watering, but its importance value reduced with recruitment of other species as the wet season advanced, which presented it as an inferior competitor and explains its reduced availability in the wild at the peak of wet season and in the dry season. For cultivation purposes therefore, Phyllanthus amarus should be grown in well-drained soils with regular weeding carried out and with adequate moisture provided.